The Influence of Experiential Marketing, Promotion and Price on the Purchase Decision of Auky Gift Surabaya Product - Yessy Kurniawati; Muhammad Anang Firmansyah; Siti Maro'ah (International Conference on Economics, Management, Business, and Accounting, 2025)
This study examines The Impact of Experiential Marketing, Promotion, and Price on Consumer Purchasing Decisions for Auky Gift Surabaya. Using a quantitative survey of 100 buyers, data were analyzed with multiple linear regression via SPSS 25. Results show that experiential marketing and promotion significantly and positively affect purchasing decisions, while price has no significant effect. Collectively, the three variables influence consumer choices. The study is limited to a single company with a small sample, reducing generalizability. Future research should include wider objects and larger samples to improve validity. The novelty lies in integrating Experiential Marketing, Promotion, and Price in the context of gift products, contributing to marketing literature and offering practical insights for businesses to strengthen consumer decisions through experiential and promotional strategies